TEACHERS ENGAGEMENT GURU MADRASAH ALIYAH DALAM PEMBELAJARAN DI MASA PANDEMI COVID-19 (TEACHERS ENGAGEMENT OF MADRASAH ALIYAH’S TEACHERS IN LEARNING DURING COVID-19) - Aji Sofanudin; Rahmawati Prihastuti; Ayon Diniyanto (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2021)
The Covid-19 pandemic has forced all aspects of life to change, including learning at Madrasah Aliyah. This study aims to determine the differences of teacher engagement from gender perspective and certification status of teachers in Madrasah Aliyah at Tegal regency. This study used a mixed method with 302 research participants of teachers at Madrasah Aliyah. The research findings show that teachers’ engagement consists of five aspects, namely vigor, dedication, absorption, job satisfaction, and quitting intention. By using these five aspects, it is known that there are differences in teacher engagement between male and female teachers. Male teachers have higher teacher engagement scores than female teachers. Mean teacher engagement for male teachers was 4.62 while female teachers were 4.55. rh value is 0.209, it is greater than the value of rtabel at either 5% or 1% significance. This shows that there are differences in the value of teacher engagement between men and women. Meanwhile, the mean of teachers who were certified (4.73) was higher than uncertified teachers (4.48). The rh value of -0.001 indicates that there is no difference in the value of teacher engagement between certified and uncertified teachers in Madrasah Aliyah at Tegal regency. This finding deserves attention from policymakers at the Ministry of Religious Office of Central Java Province.